2015
DOI: 10.1146/annurev-economics-080614-115510
|View full text |Cite
|
Sign up to set email alerts
|

Is College a Worthwhile Investment?

Abstract: This article surveys the existing evidence on the return to a college education and offers new calculations based on recent data. We focus on an individual's decision and outline the standard conceptual framework used by economists to analyze investments in education. We then compare alternative estimates of the value of a college education in the literature and reconcile them with our own preferred estimates. We also conduct a selective review of the literature seeking to estimate the causal effects of colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 97 publications
2
23
0
Order By: Relevance
“…Reviews of existing research on returns to higher education offer support for this possibility. Even marginal students who enter college appear to exhibit large returns, on average (Barrow & Malamud, 2015;Hout, 2012;Oreopoulos & Petronijevic, 2013). 28 The finding that low-cost assistance matters suggests that, for some students, enrollment decisions do not represent well thought out investment choices.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews of existing research on returns to higher education offer support for this possibility. Even marginal students who enter college appear to exhibit large returns, on average (Barrow & Malamud, 2015;Hout, 2012;Oreopoulos & Petronijevic, 2013). 28 The finding that low-cost assistance matters suggests that, for some students, enrollment decisions do not represent well thought out investment choices.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a rigorous study done in Norway showed that a university degree in a career related to science, technology, engineering, or math increased earnings 11 percent per year of study more than a degree in the social sciences (Kirkeboen, Leuven, and Mogstad, 2016). Evidence from the United States also suggests that the returns to different fields of study vary significantly (Barrow and Malamud, 2015).…”
Section: The Difference Makersmentioning
confidence: 99%
“…In particular, a rigorous study done in Norway showed that a university degree in a career related to science, technology, engineering, or math increased earnings 11 percent per year of study more than a degree in the social sciences (Kirkeboen, Leuven, and Mogstad, 2016). Evidence from the United States also suggests that the returns to different fields of study vary significantly (Barrow and Malamud, 2015).Finally, limited evidence on the role of learning-by-doing suggests that this is an important factor for skills development. In particular, a study in Germany showed that the average worker enjoys a cumulative increase of 2 percent per each additional year of work experience (Dustmann and Meghir, 2005).…”
mentioning
confidence: 99%
“…This can be done by screening on the basis of observable student characteristics, such as exam scores and grades. Empirically, selective nonprofit colleges generate much higher earnings premia relative to for-profit schools (Barrow & Malamud 2015). However, even in the absence of higher earnings premia, nonprofit schools can attract higher-ability students by offering lower net tuition through tapping their endowment assets.…”
Section: Adding Nonprofit Educational Institutions To the Frameworkmentioning
confidence: 99%